2017
DOI: 10.3892/mco.2017.1437
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiated endometrial carcinoma: A report of three cases and review of the literature

Abstract: Abstract. Dedifferentiated endometrial carcinoma, which is defined microscopically as the co-existence of undifferentiated carcinoma and grade 1 or 2 endometrioid adenocarcinoma, is an aggressive type of cancer regardless of the percentage of undifferentiated components. It is reported that undifferentiated carcinoma comprises 9% of endometrial carcinoma. The percentage of dedifferentiated endometrial carcinoma has been hypothesized to be 40% of undifferentiated carcinoma. A precise pathological diagnosis is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Dedifferentiation is well-established in soft tissue and bone tumors, and more recently in epithelial tumors. Dedifferentiation is not uncommon in uterine or ovarian endometrioid carcinoma, and typically associated with an aggressive clinical course [17]. The dedifferentiation conception in anaplastic nodules is supported by our molecular and immunohistochemical analysis.…”
Section: Discussionsupporting
confidence: 69%
“…Dedifferentiation is well-established in soft tissue and bone tumors, and more recently in epithelial tumors. Dedifferentiation is not uncommon in uterine or ovarian endometrioid carcinoma, and typically associated with an aggressive clinical course [17]. The dedifferentiation conception in anaplastic nodules is supported by our molecular and immunohistochemical analysis.…”
Section: Discussionsupporting
confidence: 69%
“…Preoperative diagnosis of DEC is difficult by only endometrial curettage [ 8 ]. Our literature review showed that almost all cases were diagnosed by surgical specimens and only two cases were diagnosed by endometrial biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…An association between DEC and Lynch syndrome has been previously reported [ 6 ]. Yokomizo et al examined the immunohistochemistry for DNA mismatch-repair (MMR) proteins in three cases diagnosed as DEC and demonstrated the loss of MMR protein expression in the UC components of these patients [ 8 ]. Thus, the authors emphasized the importance of assessing the genetic background of patients with DEC.…”
Section: Discussionmentioning
confidence: 99%
“…No reports systematically explored the efficacy of treatment such as surgery and adjuvant therapy [8,13,19]. Therefore, the present authors aimed to systematically review and investigate appropriate treatments, using current available information.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated the clinical outcome regarding DC [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. DC has been assumed to be an aggressive tumor that induces a poor clinical outcome regardless of aggressive treatment that includes surgery and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%